1991
DOI: 10.1126/science.251.4999.1348
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Genetic Classification of Zooxanthellae and the Evolution of Animal-Algal Symbioses

Abstract: Zooxanthellae are unicellular algae that occur as endosymbionts in many hundreds of marine invertebrate species. Because zooxanthellae have traditionally been difficult to classify, little is known about the natural history of these symbioses. Zooxanthellae were isolated from 131 individuals in 22 host taxa and characterized by the use of restriction fragment length polymorphisms (RFLPs) in nuclear genes that encode small ribosomal subunit RNA (ssRNA). Six algal RFLPs, distributed host species specifically, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
323
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 395 publications
(334 citation statements)
references
References 22 publications
11
323
0
Order By: Relevance
“…It is now recognized that different genotypes of zooxanthellae within corals show a distinct ecological zonation with depth (Rowan and Knowlton 1995). The zooxanthellae within the congenerics used in this study from both depths have all been identified as belonging to clade C (Rowan and Powers 1991;Rowan and Knowlton 1995) by restriction fragment length polymorphisms of 24s rDNA (Lesser unpubl. data).…”
Section: Discussionmentioning
confidence: 90%
“…It is now recognized that different genotypes of zooxanthellae within corals show a distinct ecological zonation with depth (Rowan and Knowlton 1995). The zooxanthellae within the congenerics used in this study from both depths have all been identified as belonging to clade C (Rowan and Powers 1991;Rowan and Knowlton 1995) by restriction fragment length polymorphisms of 24s rDNA (Lesser unpubl. data).…”
Section: Discussionmentioning
confidence: 90%
“…This perception began when Rowan et al (1997) found that 'Clade A' increased its proportional representation following a natural bleaching event, and Toller et al (2001) reported that 'Clade A' was common in Orbicella (formerly Montastraea) samples taken during bleaching experiments and from tissues with yellow-band disease (YBD, sometimes called yellowblotch disease). Although Toller et al (2001) recognized the potential for cryptic diversity within clades (both Rowan & Powers (1991) and Toller et al (2001) acknowledged that the small subunit rDNA did not resolve species), they presumed, in the absence of evidence to the contrary, that their 'Clade A' entity was the same as the species most often found on the tops of shallow Orbicella colonies, currently known as Symbiodinium A3 Kemp et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenies such as those based on nuclear ribosomal deoxyribonucleic acid (rDNA) divide the genus into several large clades (Rowan and Powers 1991). The internal transcribed spacer regions 1 and 2 (ITS1 and ITS2) further characterize numerous subcladal genetically distinct types (Lajeunesse 2001;van Oppen et al 2001), which closely approximate physiologically and ecologically distinct populations (Lajeunesse 2002;Warner et al 2006;Frade et al 2008).…”
mentioning
confidence: 99%